2013
DOI: 10.5152/akd.2013.068
|View full text |Cite
|
Sign up to set email alerts
|

Impaired coronary flow reserve evaluated by echocardiography is associated with increased aortic stiffness in patients with metabolic syndrome: an observational study

Abstract: Impaired coronary flow reserve evaluated by echocardiography is associated with increased aortic stiffness in patients with metabolic syndrome: an observational studyMetabolik sendromlu hastalarda ekokardiyografik olarak gösterilen bozulmuş koroner akım rezervi artmış aort sertliği ile ilişkilidir: Gözlemsel bir çalışma ABSTRACTObjective: Metabolic syndrome (MetS) is a strong predictor of cardiovascular events and coronary flow reserve (CFR), an indicator of microvascular function, has been found to be impair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
2
1
Order By: Relevance
“… 5 - 7 , 11 , 18 - 22 EFT is increased in patients with inflammation, advanced age, obesity, hypercholesterolemia, hypertension, atrial fibrillation, diabetes mellitus and metabolic syndrome. 3 , 4 , 10 , 23 - 27 In our study, there was no significant difference between the groups in terms of blood glucose and body mass index. The number of patients diagnosed with metabolic syndrome, diabetes and hypertension was similar between groups ( Table 1 ).…”
Section: Discussioncontrasting
confidence: 47%
“… 5 - 7 , 11 , 18 - 22 EFT is increased in patients with inflammation, advanced age, obesity, hypercholesterolemia, hypertension, atrial fibrillation, diabetes mellitus and metabolic syndrome. 3 , 4 , 10 , 23 - 27 In our study, there was no significant difference between the groups in terms of blood glucose and body mass index. The number of patients diagnosed with metabolic syndrome, diabetes and hypertension was similar between groups ( Table 1 ).…”
Section: Discussioncontrasting
confidence: 47%
“…Similarly, microvascular dysfunction of the coronary arterioles as evaluated using abnormal transthoracic Doppler echocardiography after intravenous infusion of the adenosine uptake inhibitor dipyridamole was described in a cohort of patients with MS (i.e., increased levels of LDL and triglycerides but reduced levels of HDL cholesterol)(Pirat et al, 2008). In a cohort of forty-five MS patients, a reduced coronary flow reserve after infusion of adenosine was also determined by echocardiography, which was correlated with body mass index, waist circumference, fasting glucose levels, more sensitive C-reactive protein and the HDL and triglycerides levels(Tok et al, 2013). Another study with fourteen dyslipidaemic patients showed that after intravenous adenosine infusion, the myocardial blood flow and endothelial-dependent vasodilation of coronary vessels was reduced in those subjects as measured by PET(Alexanderson et al, 2010).…”
mentioning
confidence: 99%
“…In this study, the evaluation of aortic stiffness was performed via relating change in diameter of aorta to distending pressure, not assessed by pulse wave velocity (PWV) (15). In previous studies, significant correlations between CFR and aortic stiffness assessed by PWV have been demonstrated in patients with hypertension and coronary artery disease.…”
mentioning
confidence: 99%